Design and evaluation of albumin nanoparticles for the delivery of a novel β-tubulin polymerization inhibitor - Alessandra Spada; Jaber Emami; Foroughalsadat Sanaee; Maral Aminpour; Igor, M Paiva; Jack Tuszynski; Afsaneh Lavasanifar (Frontiers Media S.A., 2021)
Purpose: The ultimate goal of this study is to develop a novel delivery system for a new potent cytotoxic compound, CCI-001, with anti-b tubulin activity, so that the drug can be effectively administered and at the same time its harmful side effects can be reduced. Methods: In the current study, CCI-001 was loaded into serum albumin (SA), using a modified desolvation method, generating CCI-001-SA nanoparticles. Both bovine and human SA were used for the encapsulation of this drug candidate. Optimum conditions for drug loading were achieved when already formed and crosslinked albumin nanoparticles were incubated overnight at 37°C with CCI-001 solutions. The CCI-001-loaded albumin nanoparticles were assessed for average particle diameter and polydispersity, zeta potential, drug loading, in vitro release, morphology and cell toxicity against SW620 and HCT116 colorectal cancer cells. Results: The spherical nanoparticles obtained were negatively charged (~ -30 mV) and had an average diameter of ~ 130 nm, with a narrow size distribution. The in vitro release of CCI-001 from the albumin nanoparticles showed a sustained release pattern over 24 hours without any initial burst release, compared to the fast release of the free drug under experimental conditions. No difference between the SA from the two species in terms of CCI-001 loading was observed. However, a significant difference was observed between the release profiles of CCI-001 from drug-loaded HSA and drug-loaded BSA nanoparticles with HSA nanoparticles showing slower drug release (mean release time, MRT, values of 5.14 ± 0.33 h and 6.88 ± 0.15 h for BSA-NPs and HSA-NPs, respectively, P < 0.01). Cellular toxicity studies showed higher cytotoxicity for CCI-001-SA compared to the free drug (IC50s of 0.62 ± 0.31 nM vs 2.06 ± 0.29 nM in SW620 cells and 0.9 ± 0.1 nM vs 4.2 ± 0.2 nM in HCT116 cells, for CCI-001-HSA NPs and free drug, respectively). Therefore, despite the low drug content level in the HSA nanoparticles of CCI-001, the formulation provides relevant concentrations for further in vivo studies in animal models due to high drug potency. Conclusions: The data support the potential use of albumin as a nanocarrier for CCI-001 in biological systems.